1988
DOI: 10.1016/0741-5214(88)90136-x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics and prostacyclin release in the early phases of aortic surgery: Comparison of transabdominal and retroperitoneal approaches

Abstract: Although the retroperitoneal aortic approach (RP) is advocated to reduce myocardial ischemia and cardiac-related death, inadequate physiologic data exist to support this contention. As the aorta is exposed via the transabdominal approach (TA) we noted some patients have manifested reduced systemic vascular resistance (SVR) associated with tachycardia, reduced blood pressure, and facial flushing. To determine whether RP offered physiologic advantages over TA we compared cardiac dynamics and blood levels of 6-ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(11 citation statements)
references
References 11 publications
1
9
0
1
Order By: Relevance
“…In accordance with the present study, several investigators have demonstrated a significant increase in MAP during laparoscopic procedures [11,12]. Persistent elevation of MAP during LC may be due to many causes such as release of catecholamine and other humoral factors (dopamine [13], vasopressin [14], rennin [15], and cortisol [16] ), vasoconstriction caused by thromboxane release due to mesenteric stretching and compression of abdominal aorta by pneumoperitoneum [17], and lastly due to hypercarbia [18].…”
Section: Discussionsupporting
confidence: 85%
“…In accordance with the present study, several investigators have demonstrated a significant increase in MAP during laparoscopic procedures [11,12]. Persistent elevation of MAP during LC may be due to many causes such as release of catecholamine and other humoral factors (dopamine [13], vasopressin [14], rennin [15], and cortisol [16] ), vasoconstriction caused by thromboxane release due to mesenteric stretching and compression of abdominal aorta by pneumoperitoneum [17], and lastly due to hypercarbia [18].…”
Section: Discussionsupporting
confidence: 85%
“…In recent years, as an alternative approach, the retroperitoneal (RP) exposure of the aorta has been advocated by many authors to avoid entering the peritoneum ; thus providing less physiologic trauma and a reduced postoperative morbidity (2)(3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] The mucosa of the intestine and the endothelium of blood vessels contain enzymes capable of synthesizing prostaglandins, production of which may be initiated by neural, ischemic, toxic, or mechanical stimuli. [ 24 ] The generation of these vasoactive prostaglandins can therefore induce splanchnic ischemia with subsequent disruption of mucosal integrity and increased intestinal permeability. Therefore, intestinal manipulation may lead to the endotoxemia detected in the systemic circulation, in patients undergoing colorectal surgery.…”
Section: Discussionmentioning
confidence: 99%